2010
DOI: 10.1111/j.1447-0756.2010.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of p53 and Ki‐67 (MIB‐1) expressions with clinicopathological features and prognosis of early stage cervical squamous cell carcinomas

Abstract: Ki-67 expression is an independent prognostic parameter for RFS in patients with early stage squamous cell carcinoma of the uterine cervix. Ki-67 expression at or above the cut-off point of 30.0% had significantly poorer RFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
1
20
1
Order By: Relevance
“…Hunt et al's study [4] showed the corresponding figures as 33 and 36 %, respectively. There was no relation between p53 overexpression and prognosis in cervical cancer [4,8]. The present study shows lack of relationship between p53 overexpression and prognosis in the cervical cancer patients.…”
Section: P53 Expression and Histopathology Of Cervical Cancercontrasting
confidence: 69%
See 1 more Smart Citation
“…Hunt et al's study [4] showed the corresponding figures as 33 and 36 %, respectively. There was no relation between p53 overexpression and prognosis in cervical cancer [4,8]. The present study shows lack of relationship between p53 overexpression and prognosis in the cervical cancer patients.…”
Section: P53 Expression and Histopathology Of Cervical Cancercontrasting
confidence: 69%
“…In the present study, p53 upregulation was found in 28.94 % of cases in blood and 27.27 % of tissue. p53 overexpression was present in 25.5 % of cases in Oka et al's study [7], 33.6 % in Hanprasertpong J et al's study [8], and 14.0 % in Busby-Earle et al's study [9].…”
Section: Observationsmentioning
confidence: 84%
“…As an established marker for cell proliferation, Ki67 has been suggested to be a predictor for high-risk HPV infection and an independent prognostic parameter for recurrence-free survival of CC (16,17). Our findings showed that the Ki67-positive cells were mainly located in the surrounding areas of cancer nests or in invaded cancerous tissues, implying active growth of the cells in these areas.…”
Section: Discussionmentioning
confidence: 54%
“…In patients with cervical SCC, Hanprasertpong et al (90) found Ki-67 expression in 81.3% of cases and p53 expression in 33.6%. There was a significant correlation between p53 and Ki-67.…”
Section: Biomarkers For the Prognostic Prediction Of Cervical Cancermentioning
confidence: 99%